Antenatal Magnesium Sulfate, Necrotizing Enterocolitis, and Death among Neonates < 28 Weeks Gestation - Manijeh Kamyar; Erin A. S. Clark; Bradley A. Yoder; Michael W. Varner; Tracy A. Manuck (Thieme Medical Publishers, Inc., 2016)
Abstract Objective This study aims to examine the relationship between antenatal magnesium sulfate (MgSO4) and neonatal death and/or severe necrotizing enterocolitis (NEC) among infants < 28 weeks. Methods Secondary analysis of a multicenter randomized trial of antenatal MgSO4 versus placebo administered to women to prevent death and cerebral palsy. Neonates < 28 weeks were included. The primary outcome was neonatal death before NICU discharge, and/or severe NEC (Bell criteria stage II/III). Neonates with and without death/severe NEC were compared. Results A total of 697 neonates met the criteria. Out of which 150 (21.5%) died and/or were diagnosed with severe NEC. Antenatal MgSO4 exposure was not associated with death/severe NEC in infants < 28 weeks. In a subgroup analysis of neonates < 26 weeks, treatment group assignment to antenatal MgSO4 was associated with an increased odds of death/severe NEC (adjusted odds ratio: 1.90, 95% confidence interval: 1.12-3.22, p = 0.017). Conclusions Among neonates < 26 weeks, antenatal MgSO4 was associated with death and severe NEC. Further prospective study in larger populations is needed.